2009
DOI: 10.1083/jcb.200810055
|View full text |Cite
|
Sign up to set email alerts
|

Localization of recombination proteins and Srs2 reveals anti-recombinase function in vivo

Abstract: Homologous recombination (HR), although an important DNA repair mechanism, is dangerous to the cell if improperly regulated. The Srs2 “anti-recombinase” restricts HR by disassembling the Rad51 nucleoprotein filament, an intermediate preceding the exchange of homologous DNA strands. Here, we cytologically characterize Srs2 function in vivo and describe a novel mechanism for regulating the initiation of HR. We find that Srs2 is recruited separately to replication and repair centers and identify the genetic requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 91 publications
(120 reference statements)
6
111
0
1
Order By: Relevance
“…Consistent with this suggestion, Rothstein and colleagues (Burgess et al 2009) recently demonstrated that during mitosis the in vivo depletion of Srs2 permits Rad54, thus possibly Rad51, loading onto chromatin, even in the absence of Rad52, indicating that Srs2 depletion reduces the requirement for Rad52. Moreover, the deletion of the SRS2 gene in mitosis suppresses DNA damage defect of the rad55 or rad57 mutants (Liu et al 2011).…”
Section: Srs2 Removes Rad51 From Chromosomes During Meiotic Recombinasupporting
confidence: 51%
See 2 more Smart Citations
“…Consistent with this suggestion, Rothstein and colleagues (Burgess et al 2009) recently demonstrated that during mitosis the in vivo depletion of Srs2 permits Rad54, thus possibly Rad51, loading onto chromatin, even in the absence of Rad52, indicating that Srs2 depletion reduces the requirement for Rad52. Moreover, the deletion of the SRS2 gene in mitosis suppresses DNA damage defect of the rad55 or rad57 mutants (Liu et al 2011).…”
Section: Srs2 Removes Rad51 From Chromosomes During Meiotic Recombinasupporting
confidence: 51%
“…This might be simply due to delayed repair events. Moreover, overexpression of Srs2 decreases the Rad54-GFP that binds to DSBs (Burgess et al 2009), which indirectly supports this idea that Srs2 disrupts Rad51 on the mitotic DSB site, given that Rad54 binds to Rad51 ensembles (Colavito et al 2009). For this study, we combined cytological characterization of chromosome spreads and genetic overexpression of Srs2 during meiosis to demonstrate that Srs2 could disrupt Rad51 filaments on chromosomes in vivo.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…At the C‐terminus, Srs2 contains a variety of regulatory motifs, which are modulated through post‐translational modifications and/or required for the interactions of Srs2 with other proteins, including PCNA, and these are important for its role at replication forks (Papouli et al , 2005; Pfander et al , 2005; Burgess et al , 2009) and regulation of the D‐loop extension (Burkovics et al , 2013). However, most of the C‐terminus was not required for the role of Srs2 in DSB repair via de novo telomere addition, BIR and SSA (Fig 8A–D).…”
Section: Resultsmentioning
confidence: 99%
“…The Srs2 helicase inhibits HR machinery by disassembling Rad51 filament and reducing DNA extension, as demonstrated in vitro (Burkovics et al , 2013; Krejci et al , 2003; Veaute et al , 2003). This function is believed to be important for repression of excessive recombination, particularly at replication forks where Srs2 is recruited and regulated through its C‐terminal domain (Papouli et al , 2005; Pfander et al , 2005; Burgess et al , 2009). Loss of Srs2 results in a paradoxical phenotype.…”
Section: Introductionmentioning
confidence: 99%